Respuesta :

Answer:

The solution to the initial value problem is [tex]y(t)=\frac{3t^{10}+37}{5t^9}[/tex]

Step-by-step explanation:

We have the following differential equation

[tex]t\frac{dy}{dt}+9y=6t, \:{y(1)=8}[/tex]

This is a linear differential equation because we can made to look like this:

[tex]\frac{dy}{dt}+P(t)y=Q(t)[/tex]

where [tex]P(t)[/tex] and [tex]Q(t)[/tex] are functions of t.

The solution process for a first-order linear differential equation is as follows.

1. Put the differential equation in the correct initial form.

2. Find the integrating factor, [tex]\mu(t)[/tex].

3. Multiply everything in the differential equation by [tex]\mu(t)[/tex] and verify that the left side becomes the product rule [tex](\mu(t)y(t))'[/tex] and write it as such.

4. Integrate both sides, make sure you properly deal with the constant of integration.

5. Solve for the solution [tex]y(t)[/tex].

Applying the solution process, we have

1. We need to get the differential equation in the correct form.

[tex]\frac{dy}{dt}+\frac{9}{t} y=6[/tex]

From this we can see that [tex]p(t)=\frac{9}{t} [/tex]

2. The integrating factor is [tex]\mu(t) = e^{\int {p(t)} \, dt }[/tex]

[tex]\mu(t) = e^{\int {p(t)} \, dt }\\\mu(t) = e^{\int {\frac{9}{t} } \, dt }\\\mu(t) = e^{9\ln \left|t\right|}\\\mu(t) = t^9[/tex]

3. Now multiply all the terms in the differential equation by the integrating factor and do some simplification.

[tex]\frac{dy}{dt}+\frac{9}{t} y=6\\t^9(\frac{dy}{dt})+t^9(\frac{9}{t} y)=6t^9\\(t^9y)'=6t^9[/tex]

4. Integrate both sides and don't forget the constants of integration that will arise from both integrals.

[tex]\int {(t^9y)'} \, dt =\int {6t^9} \, dt \\\\t^9 y+k=\frac{3t^{10}}{5}+c\\\\t^9 y=\frac{3t^{10}}{5}+c-k\\\\t^9 y=\frac{3t^{10}}{5}+d\\\\y=\frac{3t^{10}+5d}{5t^9}[/tex]

5. To find the solution we are after we need to identify the value of d that will give us the solution we are after. To do this we simply plug in the initial condition which will give us an equation we can solve for d.

[tex]8=\frac{3(1)^{10}+5d}{5(1)^9} \Rightarrow d=\frac{37}{5}[/tex]

So, the actual solution to the initial value problem is

[tex]y(t)=\frac{3t^{10}+37}{5t^9}[/tex]

ACCESS MORE